The clinical performance of monoshade resin composite as posterior restoration: a randomized controlled clinical trial - Ruba Salah Anwar; Yasser Fathi Hussein; Mona Riad (Scientific Reports)
Abstract The aim of this study was to assess the clinical performance of a monoshade universal resin composite as posterior restoration. Twenty adult patients having at least two carious lesions related to posterior teeth were selected. Each patient was provided with a monoshade resin composite (Omnichroma) and polyshade nanohybrid resin composite (Tetric® N-Ceram) for class I or II restorations. The performance of these restorations was assessed at 1, 3, 6, 9, and 12 months according to the modified United States Public Health Service (USPHS) criteria. Statistical analysis was carried out employing the Friedmann test and the Wilcoxon signed-rank test, with a significance level of p = 0.05. None of the restorations exhibited any clinical conditions warranting replacement. The monoshade universal group revealed prevalence of (Bravo) scores concerning the anatomic form, surface texture and post-operative sensitivity through the follow-up period (P = 0.317). For color match and color stability, the polyshade group revealed a statistically significantly higher incidence of (Alpha) scores after 9 and 12 months (P = 0.025). After 12-months of follow-up, the monoshade universal resin composite demonstrated satisfactory clinical performance. It can serve as a viable substitute for polyshade nanohybrid composite where chair side time is an essential concern.